2021
DOI: 10.3390/pharmacy9040174
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Tenets of PRN Medicines Management in Healthcare Settings: A Clinical Perspective

Abstract: Prescription and administration of pro re nata (PRN) medications has remained a poorly discussed area of the international literature regarding ethical tenets influencing this type of medication practice. In this commentary, ethical tenets of PRN medicines management from the clinical perspective based on available international literature and published research have been discussed. Three categories were developed by the authors for summarising review findings as follows: ‘benefiting the patient’, ‘making well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 88 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…There were a number of factors contributing to PRN medicine use and reasons to proceed with PRN administration. Unfortunately, it was found that these were not necessarily patient‐oriented and evidence‐based, a worrying issue when short‐term effects and possible prolonged harm needs to be balanced (Vaismoradi et al, 2021). This finding concurs with the last systemic review which indicated that PRN medication's administering and prescribing varied based on the situation, organization, and individuals (Morkunas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There were a number of factors contributing to PRN medicine use and reasons to proceed with PRN administration. Unfortunately, it was found that these were not necessarily patient‐oriented and evidence‐based, a worrying issue when short‐term effects and possible prolonged harm needs to be balanced (Vaismoradi et al, 2021). This finding concurs with the last systemic review which indicated that PRN medication's administering and prescribing varied based on the situation, organization, and individuals (Morkunas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Psychotropic PRN medications include antipsychotics, benzodiazepines, and sedatives, and these are commonly used in mental health settings in response to agitation, anxiety, and insomniac conditions (Jimu & Doyle, 2019). The advantage of psychotropic PRN medications is to enable nurses to respond to the patients' immediate clinical needs rather than waiting for regular dose administration (Harper et al, 2017), and from the patient's point of view, they can ask for PRN medication to control their symptoms on an as‐needed basis (Vaismoradi et al, 2021). The disadvantages of psychotropic medication involve the potential negative outcomes for patients' health, such as metabolic syndrome, morbidity, polypharmacy, drug dependence, overuse, and adverse drug interactions (Barr et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations